William Henry Elsegood scrapbook - Elsegood, William Henry, 1795-
Bound volume (circa 100 items) containing "The Military Magazine and Record of the Volunteers of the United States" (1839 Mar.-1840 Feb.) interleaved with clippings, printed notices, military orders, and other documents relating chiefly to local military affairs in Philadelphia and to Elsegood's service with the 19th regiment Hibernia Greens. Included in the magazine are regimental histories and engravings of various uniforms.
Militia officer.
Collection material in English.
Keywords: Pennsylvania -- Militia; Philadelphia (Pa.) -- History, Military; Military uniforms; Military Magazine and Record of the Volunteers of the United States; Militia officers